THE RELATIONSHIP BETWEEN THE TEACHER PERSONALITY COMPETENCIES AND THE ATTITUDE OF THE LEARNER - Wandini, Intan; Abdurahkman, Omon (DIDAKTIKA TAUHIDI: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The attitude of learners can be influenced by a teacher as an educator, because teachers can direct and guide learners to be able to control his attitude in the control. Which is meant personality competence is full of changes that have a personality that wise, steady, authoritative, adult, and noble character. This study aims to determine whether there is a relationship between teacher personality competence with the attitude of learners. The type of research used is quantitative research. This study is a functional relationship that aims to determine the relationship of independent variables with the dependent variable, Data collected using questionnaires and interviews. The result of research obtained data of filling of questionnaire from 30 teacher and 70 student use t test obtained tcount = 4.625 > ttable = 1.988 so the relationship between the teacher personality competence and the attitude of the learners is significant. Regression equation of from Y =Â  68.873 + 0.132X. this study received an effective contribution R2 = 0.028 which indicates the existence 2.8% the attitude variabel of the student is influenced by teacher personality competence, 97.2 % are influenced by other factors that were not analyzed in the research, and result of correlation analysis between teacher personality competence with attitude of student obtained value equal to 0.409 showing moderate relationship between teacher personality competence with attitude of student at SDN Leuwiliang 01 and SDN Leuwiliang 04.